Breast cancer treatment and recovery: pets' roles as emotional buffers and stressors - Lori R. Kogan; Jennifer Currin-McCulloch; Linda S. Cook (BMC, 2023)
Abstract Background Research suggests pets foster affection, connection, and physical activity, yet has failed to address the challenges people diagnosed with cancer face in caring for their pets. The objective of this study was to better understand how pets serve as emotional buffers and/or stressors for people diagnosed with breast cancer, and how their ability to meet their pet's needs affects their well-being. Methods A cross-section study of people diagnosed with breast cancer in the United States was conducted. Adults diagnosed with stages 0 (in situ) -IV breast cancer and currently the primary guardian of at least one dog or cat and owned the animal(s) for at least 6 months, were recruited for the study. A total of 211 responses, obtained between July - November 2022 were analyzed. The survey included questions about participants' demographics; attachment to their pets; physical, emotional, and functional well-being; social support received from their pet; and 'pet parenting' concerns. Descriptive statistics were calculated to describe participants' demographics. Multiple regression analyses were conducted to determine predictors of pet attachment, well-being, support from pet, and 'pet parenting' concerns. Results People diagnosed with breast cancer derive substantial support from their pets (80% feel their pet makes them feel loved, needed, and offers a positive presence in the home), yet only 50% of participants feel this relationship is supported by their medical team. Controlling for owner demographics, heightened levels of pet-related guilt and concerns, along with lower perceived support from their pet, are all significant predictors of a lower quality of life. Conclusions Findings highlight the benefits pets offer people diagnosed with breast cancer, yet also the distress they feel in trying to meet their pet's needs. Assessment conversations about pet ownership, including pet-related support systems, are needed to validate people's concerns and support the identification and development of pet support teams. Medical team facilitated discussions about pet care needs is suggested to demonstrate support for the pet-parent bond and help normalize feelings of guilt related to challenges in meeting their pet's needs. These discussions could be aided through the development of research-driven intervention strategies and online, freely accessible targeted tools.